CovaModeler: A multi-user tool for modelling cooperative processes. (1st January 2003) - Hsieh, Yufeng; Shi, Meilin; Yang, Guangxin
Modelling collaborative processes is a complex task because it may involve many people with different backgrounds, each having their own focuses and interests. To get a perfect process description, a mechanism must be provided to support the cooperation among these people. It is in this sense that we declare that process modelling by itself is a collaborative process, which is neglected in existing modelling tools. This paper summarises the characters of this special process, then presents the policies needed to support the efficient cooperative modelling of processes so that perfect process descriptions can be produced. These policies are implemented in CovaModeler, which is a multi-user tool for Cova-based process collaborative modelling.